Consumers' behaviors when eating out: Does eating out change consumers' intention to eat healthily?. Issue 3 (2014) - ,; ,
Abstract : Purpose – The present study aimed to discover whether there are any differences among people in healthy eating and nutrition consciousness when they eat out at restaurants. Also, the study aimed to determine what relationship exists between consumers' lifestyle and their behavioral intention to eat healthily when dining out. In addition, the study investigated the relationships between restaurant attributes and consumers' intention to eat healthily when dining out.Design/methodology/approach – This study posits that restaurant attributes have an impact on consumers' intention to order healthy meals at a restaurant. Questionnaires were distributed and collected over a two‐month period in south Florida. Respondents were asked to indicate on a five‐point scale their considerations when selecting a restaurant and particular ingredients in the food when dining out. The study analyzed the data using one‐way ANOVA and Games‐Howell test in order to find that considerations about nutritional components when choosing a meal at a restaurant. Also, multiple regression was run to determine the relationship between lifestyle and restaurant attributes and intention to order healthy food at a restaurant.Findings – Most of the respondents (76.5 percent) were concerned about their weight; however, only 26.7 percent of the respondents were actually on a diet. Of the respondents 33 percent knew about MyPyramid (USDA), which is an updated version of the Food Pyramid (USDA). Based on the results of one‐way ANOVA and Games‐Howell test, the study found that considerations about nutritional components when choosing a meal at a restaurant differed according to consumers' knowledge of health issues, weight concerns, gender, age, and marital status. Also, the results of multiple regression suggested that lifestyle, offering variety of healthy food, and services were significant predictors of consumers' intention to order healthy food at a restaurant, whereas other attributes of restaurants were not significant predictors for the ordering of healthy food.Originality/value – This study has contributed unique and extended conclusions from previous studies and has given consumers a better understanding about particular nutritional components in order for them to take advantage of the recent trend in more healthy foods being available at restaurants. The results of this study revealed that restaurants' marketing strategies for healthy food need to target consumers whose lifestyle promotes a healthy life in terms of regular exercise, dietary plans, or eating food considering the FoodPyramid, rather than target consumers whose lifestyle is less healthy. However, the results of this study also suggest that the offering of healthy food and good services do have effect on consumers' consideration to order healthy food.